2023
DOI: 10.1111/beer.12578
|View full text |Cite
|
Sign up to set email alerts
|

Family firm status and environmental disclosure: The moderating effect of board gender diversity

Abstract: Building on agency and resource‐based view theories, this study investigates the level of environmental disclosure (ED) practices of family versus non‐family firms and explores the moderating role of board gender diversity. We test our hypotheses on a 3‐year (2018–2020) panel data sample comprising 324 observations of Italian small‐ and medium‐sized enterprises traded on the Euronext Growth Milan. Findings show that, compared to non‐family firms, companies with a family firm status are characterized by lower l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 168 publications
0
3
0
Order By: Relevance
“…Their study reveals a negative association between internal control quality and audit report lag, with family directors moderating this relationship. Meanwhile, Maggi et al (2023) investigate environmental disclosure practices in family versus non-family firms and the moderating role of board gender diversity. Their research suggests that family firms tend to have lower levels of environmental disclosure, but the presence of gender-diverse boards narrows this gap, leading to higher environmental disclosure in family firms when a critical mass of women directors is present.…”
Section: Governance Factors That Influence the Disclosure's Propensitymentioning
confidence: 99%
“…Their study reveals a negative association between internal control quality and audit report lag, with family directors moderating this relationship. Meanwhile, Maggi et al (2023) investigate environmental disclosure practices in family versus non-family firms and the moderating role of board gender diversity. Their research suggests that family firms tend to have lower levels of environmental disclosure, but the presence of gender-diverse boards narrows this gap, leading to higher environmental disclosure in family firms when a critical mass of women directors is present.…”
Section: Governance Factors That Influence the Disclosure's Propensitymentioning
confidence: 99%
“…This resilience was particularly noticeable in the organizations hardest hit by the pandemic. In a further contribution to this discourse, Maggi et al (2023) analyzed environmental disclosure practices in family-and nonfamily-owned organizations, focusing on the impact of board gender diversity. They found that family-owned organizations generally had lower levels of environmental disclosure, but this gap was reduced when there was a critical mass of women directors on the board.…”
Section: Con Cep Tual Foundations: Board D Iver S It Y Re Source S A...mentioning
confidence: 99%
“…While women are often excluded from the succession process, some works have examined the role of women and daughters in succession planning (Cesaroni and Sentuti, 2018; Xian et al , 2021). Similarly, there is growing interest in looking at the impact of gender diversity in the family board of directors and board of governance, women's role in innovation and firm-level decision-making process (Maggi et al ., 2023; Ramadani et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%